Informant Reporting in Mild Cognitive Impairment: Sources of Discrepancy on the Functional Activities Questionnaire. (22nd May 2020) - Hackett, Katherine; Mis, Rachel; Drabick, Deborah A.G.; Giovannetti, Tania
Abstract: Objective: Relative to dementia, little is known about informant bias in mild cognitive impairment (MCI). We investigated the influence of informant demographic and relational characteristics on reports of everyday functioning using the Functional Activities Questionnaire (FAQ). Method: Four thousand two hundred eighty-four MCI participants and their informants from the National Alzheimer's Coordinating Center Uniform Data Set were included. Informants were stratified according to cohabitation, relationship, visit frequency, race/ethnicity, education, and sex. Informant-rated Mean FAQ score was compared across these groups using univariate general linear model analyses and post hoc tests. Interactions were tested between informant variables. The predictive contribution of informant variables to FAQ score was explored using hierarchical linear regression. Analyses covaried for participant cognition using a cognitive composite score, and for participant age, sex, and depression. Results: After controlling for participant cognition, depression, age, and sex, informant-rated FAQ scores varied significantly across all informant variables ( p's < .005, η p 2 's ≤ .033) except sex and visit frequency. FAQ scores were higher (more impaired) among informants who cohabitate with the participant, among paid caregivers, spouses, and adult children, and among informants with higher levels of education. Scores were lowest (less impaired) among Black/African American informants as compared to all other racial/ethnic groups. Conclusions: Demographic and relational characteristics of informants influence the perception and reporting of instrumental activities of daily living in adults with MCI. As everyday functioning is crucial for differential diagnosis and treatment outcome measurement, it is important to be aware of sources of informant report discrepancies.